The effect of Aeschynomene afraspera on the growth and yield of rice in Northeast Thailand - Yothin Konboon; Upasena, S.H.; Suthad Setboonsarng; Sumitra Poovarodom; New Zealand (Bangkok : Asian Institute of Technology, 1991)
The study on the effect of seed rate, age and time of incorporation of Aeschynomene afraspera on yield and growth characteristics of rice was conducted on Roi-et soil series at Ubon, Thailand under the rainfed condition . A. afraspera was planted as a pre- rice green manure at three seed rates with two ages and three times of incorporation. The rice variety KDML- 105 was transplanted after the green manure incorporation. The results show that significant differences were observed on some agronomic characteristics. With increased seed rate to 92 kilograms per hectare and delaying the age to 60 days after seeding the higher nitrogen yield, plant density, plant height, green manure biomass, straw yield, and rice grain yield were obtained. The transplanting of rice in 2 days after incorporation of green manure had a negative effect on seedling vigor and seedling survival than 14 and 21 days. Basal phosphorous fertilizer application to green manure at the rate of 50 kilograms of P2O5 per hectare significantly affected biomass production, nitrogen yield, rice straw yield, and rice grain yield.
A Thesis Submitted in Partial Fulfillment of the Requirement for the Degree of Master of Science
Thesis (M.Sc.) - Asian Institute of Technology, 1991
Keywords: Rice -- Thailand, Northeastern -- Planting